Biophysics of Development and Morphogenesis - Zoxidovich, Sobirjonov Abdusamad; Baxtiyorovich, Majlimov Farrux; Baxodirovich, Zuparov Ilxom (American Journal of Bioscience and Clinical Integrity, 2025)
This paper examines the application of biophysical models that describe biochemical reactions occurring in cells, including the kinetics of enzymatic processes, cooperative effects, and allostery. It is shown that circadian clocks are described as nonlinear self-oscillating systems that include feedback, delays, and noise.